Balaenoptera acutorostrata Lacepede 1804 - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Balaenoptera acutorostrata Lacépède, 1804. Hist. Nat. Cetacees, p. 134. TYPE LOCALITY: France, "pris aux environs de la rade de Cherbourg", Mancha. DISTRIBUTION: Worldwide: arctic to tropical waters. STATUS: CITES - Appendix I. SYNONYMS: bonaerensis, davidsoni, huttoni, minimus, rostrata. COMMENTS: Reviewed by Stewart and Leatherwood (1985). Two forms have been described from SW Pacific waters (Arnold et al., 1987). May represent two or three species (Wada and Numachi, 1991). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on pages 349-350, DOI: 10.5281/zenodo.7352970